The Anxiety, Depression and Quality of Life of Breast Cancer Patients Before and After Treatment: The Results of One Year Prospective Study - (:unkn) unknown (AVES, 2009)
Objective: Assessment of psychological reactions, psychiatric morbidity and quality of life of breast cancer patients gains importance because of the increase in breast cancer incidence and survival rate. The aim of this study was to examine anxiety, depression and quality of life in breast cancer patients during early and late postsurgical periods compared with presurgical period. Method: 84 newly diagnosed breast cancer patients were included in this prospective, two-center study. The quality of life, anxiety and depression in these patients were examined three times: before surgical treatment, at 1(st)-3(rd) month and at 9(th)-12(th) month postsurgically. The Hospital Anxiety and Depression Scale (HAD), the WHO Duality of Life Scale (WHOQOL-BREF) and a form including questions about sociodemographic status, medical and psychological status of the patients were used. Results: The mean age of patients was 52.18 +/- 11.17 years. 80.0% of all patients had both surgical and adjuvant treatment. The anxiety rates were 33.3%, 35.7% and 28.6%, and depression rates were 40.5%, 42.9% and 44.0% with respect to the evaluation time. No statistical difference was detected between the anxiety and depression rates of the three periods. The results of physical, psychological, social and general parts of quality of life scale at both early and late postoperative periods were less than the results of preoperative period (P <= 0.01). Discussion: The risk of anxiety and depression in the patients was high starting from the diagnosis date and was still high one year after the surgical treatment. It was observed that, the quality of life decreased in early postsurgical period, and started to increase from the first year after surgery,, however, it was still lower compared to the presurgical period. (Noropsikiyatri Arsivi 2009; 46: 175-81)
Keywords: Breast cancer; anxiety; depression; quality of life; psycho-oncology; LONG-TERM; PSYCHIATRIC MORBIDITY; EARLY-STAGE; HOSPITAL ANXIETY; WOMEN; PREVALENCE; DIAGNOSIS; SURVIVORS; DISTRESS; DISORDER